Private education systems in public education networks: relations to organization of work at school - Teise Garcia; Bianca Correa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
The present essay, as part of ongoing research, it is proposed to discuss the following question: what are the consequences of the purchase of private education systems for the organization of work at school? To answer this question, are being conducted case studies in teaching units from four municipal school systems that acquired from different private companies. The collection of data was completed early in the second half of 2011 and the moment they are being analyzed. In this work, therefore, we undertook a theoretical discussion questioning the relationship between the purchase of private education systems and work organization in public school.